PENGEMBANGAN MEDIA BUKU SAKU DIGITAL ASI EKSKLUSIF PADA IBU HAMIL DI DESA MAJAKERTA KABUPATEN BANDUNG (Jurnal Kesehatan Siliwangi, 2023)
Background: The low level of exclusive breastfeeding in Indonesia occurs due to the lack of knowledge of pregnant women about the importance of exclusive breastfeeding. In Majakerta Village, Bandung Regency, the scope of exclusive breastfeeding is still relatively low. Therefore, there needs to be efforts to increase knowledge in pregnant women by providing health promotion media. The role of the media is enormous in health promotion efforts. The development of exclusive breastfeeding digital pocketbook media can make pregnant women more interested and easily absorb information. Purpose: Develop exclusive breastfeeding digital pocketbook media for pregnant women in Majakerta Village, Bandung Regency. Method: This research uses the type of R&D (Research and Development) research and uses the ADDIE (Analysis, Design, Development,Implementation and Evaluation) development model. The number of samples in the study was 37 pregnant women with a total sampling technique. Results: Material eligibility was 73%, media eligibility was 93% and media eligibility on users was 85%, so it can be categorized as "very viable". Recommendation: This study should be able to conduct further tests in order to determine the effectiveness or effect of the use of exclusive breastfeeding digital pocketbook media on pregnant women.